Thyroid-associated ophthalmopathy: the role of oxidative stress - Ma, Chao; Li, Haoyu; Lu, Shuwen; Li, Xian (Frontiers in Endocrinology, 2024)
Thyroid-associated ophthalmopathy (TAO) is an autoimmune condition affecting the eyes, characterized by proptosis, extraocular muscle involvement, and in severe cases, vision impairment including diplopia, optic neuropathy, and potential blindness. The exact etiology of TAO remains elusive; however, increased oxidative stress and decreased antioxidant capacity are pivotal in its pathogenesis. Elevated oxidative stress not only directly damages orbital tissues but also influences thyroid function and autoimmune responses, exacerbating tissue destruction. This review explores the role of oxidative stress in TAO, elucidates its mechanisms, and evaluates the efficacy and limitations of antioxidant therapies in managing TAO. The findings aim to enhance understanding of oxidative stress mechanisms in TAO and propose potential antioxidant strategies for future therapeutic development.